Determinants of menu hybridization development opportunity toward food business performance / Nik Mohd Shahril Nik Mohd Nor - Nik Mohd Nor, Nik Mohd Shahril (2024)
This study investigates the complex dynamics of menu hybridization development, focusing on the impact of familiarity of food attributes, food adaptability, food integration, and their subsequent effect on food business performance in Malaysia's thriving culinary landscape. The study develops a robust conceptual framework by analyzing relevant literature and theories, including Resource-Based Theory, Social Capital Theory, and Dynamic Capability Theory. It explores the complex connections between familiarity of food attributes, food adaptation, food integration, menu hybridization development, and food business performance. In Malaysia, 319 chefs from casual restaurants all around Malaysia were surveyed using a quantitative research methodology that included a cross-sectional survey with a structured questionnaire. To evaluate hypotheses and model fit, the collected data were subjected to rigorous analysis, including descriptive statistics and Partial Least Square Structural Equation Modeling 4.0 (PLS-SEM 4). This study's findings shed light on the crucial role of food adaptation, food integration, and menu hybridization development as mediators between familiarity with food attributes and food business performance. These findings highlight the significance of these processes in Malaysia's FnB landscape formation. This study contributes to the existing body of knowledge by shedding light on the evolving landscape of menu hybridization and its effect on the performance of food businesses. It serves as a foundation for future research endeavors in the fields of food innovation, menu development, and the globalization of traditional cuisine. This study provides a comprehensive understanding of the factors driving menu hybridization and its implications for the Malaysian and global culinary industries.